Aerobic Capacity and Future Cardiovascular Risk in Indian Community from a Low-Income Area in Cauca, Colombia - Garcia-Hermoso, A (BioMed Central Ltd., 2017)
Background: Several studies indicates that children s aerobic capacity levels are predictors of the future risk of non-communicable diseases. Therefore, the aim of this study was to establish the proportion of subjects whose aerobic capacity is indicative of future cardiovascular risk in Indian-Nasa community from a low-income area in Cauca, Colombia. Methods: We performed a cross-sectional analysis of morphological component (height, weight, body mass index (BMI), waist circumference, triceps skinfold, subscapular skinfold, and body fat percent [BF%]), and the cardiorespiratory component (course-navette 20 m, shuttle run test and estimation of maximal oxygen consumption by indirect VO2max) from 576 participants (319 boys and 257 girls) aged 10 to 17.9 years, using the standardized FUPRECOL test battery. Results: We showed that the boys performed better than the girls in cardiorespiratory fitness. The proportion of subjects with an aerobic capacity indicative of future cardiovascular risk was 7.3%. By sex, 3.8% of boys and 11.7% of girls (X2 p = 0.001) displayed an unhealthy aerobic capacity in this study. Conclusion: The findings of this study that provide the first data on aerobic capacity health for Colombian Nasa Indian children and adolescents aged 10-17.9 years. Although the known loss of aerobic capacity is a serious consequence of the future risk of non-communicable diseases, the deterioration of physical fitness deserves increased attention among indigenous population. © 2017 The Author(s).